Changing paradigm of malnutrition among Bangladeshi women of reproductive age and gaps in national Nutrition Policies and Action Plans to tackle the emerging challenge - Khan, Shusmita; Haider, M. Moinuddin; Jamil, Kanta; Ahsan, Karar Zunaid; Siraj, Saiqa; Iqbal, Afrin; Angeles, Gustavo (Frontiers in Public Health, 2024)
Objective The main objective of this paper is to document the changing paradigm of malnutrition in Bangladesh and estimating how this is creating an intergenerational risk. This paper also examines national policy responses to tackle the silent epidemic of double burden of malnutrition. Methods Publicly available datasets of five Bangladesh Demographic and Health Surveys were used to see the changing paradigm of malnutrition among Bangladesh women. In addition to that, four national policies concerning, maternal and child health; and nutrition were reviewed using CDC’s 2013 Policy Analytical Framework. Results In Bangladesh, the share of ever-married women aged 15–49 who were underweight declined sharply between 2007 and 2017–2018, from 30 to 12%. In the same period, the proportion of women who were overweight or obese increased from 12 to 32%. Despite remarkable progress in reducing undernourishment among women, the share of well-nourished remained unchanged: 58% in 2007 and 56% in 2017–2018, mainly due to the shift in the dominant burden from undernutrition to overnutrition. This shift occurred around 2012–2013. Currently, in Bangladesh 0.8 million of births occur to overweight women and 0.5 million births occur to underweight women. If the current trend in malnutrition continues, pregnancies/births among overweight women will increase. Bangladesh’s existing relevant policies concerning maternal health and nutrition are inadequate and mostly address the underweight spectrum of malnutrition. Discussion Both forms of malnutrition pose a risk for maternal and child health. Underweight mothers are at risk of having anemia, antepartum/postpartum hemorrhage, and premature rupture of membranes. Maternal obesity increases the risk of perinatal complications, such as gestational diabetes, gestational hypertension, and cesarean deliveries. Currently, around 24% of the children are born to overweight/obese mothers and 15% to underweight mothers. Bangladesh should revise its national policies to address the double burden of malnutrition among women of reproductive age across pre-conception, pregnancy, and post-natal stages to ensure optimum maternal and child health.